1992
DOI: 10.1126/science.1380182
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin-Induced Inhibition of the 70-Kilodalton S6 Protein Kinase

Abstract: The immunosuppressant rapamycin inhibited proliferation of the H4IIEC hepatoma cell line. Rapamycin, but not its structural analog FK506, also inhibited the basal and insulin-stimulated activity of the p70 ribosomal protein S6 kinase. By contrast, insulin stimulation of the p85 Rsk S6 kinase and mitogen-activated protein (MAP) kinase activity were unaffected by drug. Rapamycin treatment of COS cells transfected with recombinant p70 S6 kinase completely inhibited the appearance of the hyperphosphorylated form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
426
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 632 publications
(458 citation statements)
references
References 29 publications
30
426
0
2
Order By: Relevance
“…This effect was totally abolished by rapamycin pretreatment (Fig. 1B, upper panels, lane 3), consistent with the effect of the macrolide on either endogenous or ectopically expressed p70 s6k activity (10,19,35,55). In contrast to the endogenous kinase, the p70 s6k D 3 E-E 389 mutant induced a high level of S6 phosphorylation in the absence of mitogens, which was further increased by insulin and largely resistant to rapamycin treatment (Fig.…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…This effect was totally abolished by rapamycin pretreatment (Fig. 1B, upper panels, lane 3), consistent with the effect of the macrolide on either endogenous or ectopically expressed p70 s6k activity (10,19,35,55). In contrast to the endogenous kinase, the p70 s6k D 3 E-E 389 mutant induced a high level of S6 phosphorylation in the absence of mitogens, which was further increased by insulin and largely resistant to rapamycin treatment (Fig.…”
Section: Resultssupporting
confidence: 48%
“…Much less is known regarding the identities of the kinases responsible for modulating the phosphorylation states of specific translational components or of the signalling pathways which regulate their activities. A number of recent studies have suggested that p70 s6k may be intimately involved in mediating the effect of hormones on global as well as selective patterns of translation (2, 27, 45), through the multiple phosphorylation of the 40S ribosomal protein S6 (20) and possibly the recently identified initiation factor 4E (eIF4E) binding protein, 4E-BP1 (53) or PHAS-I (40).Mitogen-induced phosphorylation and activation of p70 s6k appear to play an important role during the G 1 phase of the cell cycle (10,35,37,55,58), consistent with the putative function of p70 s6k in regulating increased S6 and 4E-BP1 phosphorylation (2,45,68). In parallel it has been demonstrated that the immunosuppressant rapamycin, a bacterial macrolide, negates mitogen-induced activation of p70 s6k by preventing the acute phosphorylation of a specific subset of sites, including T 229 , T 389 , S 404 , and S 411 (54).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum activation was obtained by 10 -6 are necessary for p70 s6K activation are same as those for the activation of MAP kinases and p90 rsk [7][8][9]. The immunosuppressant agents rapamycin and FK506 are structurally related macrolides that have been reported to inhibit proliferation and activation of T cells by binding the same cellular receptor, FK506-binding protein (FKBP) [20,[25][26][27]. It has been demonstrated that these two agents interfere with distinct signaling pathways after binding FKBP [21][22][23].…”
Section: Discussionmentioning
confidence: 96%
“…Phosphorylation of S6K1 at its carboxy-terminal regulatory domain by TOR appears to be a prerequisite for its full activation, which requires the PDK1-dependent phosphorylation at the activation loop of the catalytic domain (Belham et al, 1999). In addition to its well-known target, ribosomal protein S6 (Chung et al, 1992;Price et al, 1992), several other substrates of S6K1 have been also identified recently in mammalian cells, the roles of which are all implicated in the protein synthesis as well (Ma and Blenis, 2009). Perhaps being closely related with its regulatory role in protein synthesis, S6K1 is also known to be involved in controlling cell size.…”
Section: Introductionmentioning
confidence: 99%